Subtyping of Primary Aldosteronism in the AVIS-2 Study: Assessment of Selectivity and Lateralization - Rossitto, Giacomo; Amar, Laurence; Azizi, Michel; Riester, Anna; Reincke, Martin; Degenhart, Christoph; Widimsky, Jiri; Naruse, Mitsuhide; Deinum, Jaap; Schultzekool, Leo; Kocjan, Tomaz; Negro, Aurelio; et al. (The Journal of clinical endocrinology and metabolism, 2020)
CONTEXT: Adrenal venous sampling (AVS) is the key test for subtyping primary aldosteronism (PA), but its interpretation varies widely across referral centers and this can adversely affect the management of PA patients. OBJECTIVES: To investigate in a real-life study the rate of bilateral success and identification of unilateral aldosteronism and their impact on blood pressure outcomes in PA subtyped by AVS. DESIGN AND SETTINGS: In a retrospective analysis of the largest international registry of individual AVS data (AVIS-2 study), we investigated how different cut-off values of the selectivity index (SI) and lateralization index (LI) affected rate of bilateral success, identification of unilateral aldosteronism, and blood pressure outcomes. RESULTS: AVIS-2 recruited 1625 individual AVS studies performed between 2000 and 2015 in 19 tertiary referral centers. Under unstimulated conditions, the rate of biochemically confirmed bilateral AVS success progressively decreased with increasing SI cut-offs; furthermore, with currently used LI cut-offs, the rate of identified unilateral PA leading to adrenalectomy was as low as <25%. A within-patient pairwise comparison of 402 AVS performed both under unstimulated and cosyntropin-stimulated conditions showed that cosyntropin increased the confirmed rate of bilateral selectivity for SI cut-offs ≥ 2.0, but reduced lateralization rates (P < 0.001). Post-adrenalectomy outcomes were not improved by use of cosyntropin or more restrictive diagnostic criteria. CONCLUSION: Commonly used SI and LI cut-offs are associated with disappointingly low rates of biochemically defined AVS success and identified unilateral PA. Evidence-based protocols entailing less restrictive interpretative cut-offs might optimize the clinical use of this costly and invasive test. (J Clin Endocrinol Metab XX: 0-0, 2020).
Keywords: adrenalektomie; registry; aldosterone; Humans; diferenciální diagnóza; Cosyntropin; Adrenalectomy; nadledviny; následné studie; hormony; Diagnosis, Differential; lidé; hyperaldosteronismus; Hyperaldosteronism; Hormones; aldosteronism; kosyntropin; Retrospective Studies; Adrenal Glands; prognóza; Specimen Handling; retrospektivní studie; odběr biologického vzorku; diagnosis; Prognosis; Follow-Up Studies; adrenal vein sampling